A Simulated Mass Casualty Incident Triage Exercise: SimWars - Suzanne Bentley; Laura Iavicoli; Lorraine Boehm; George Agriantonis; Barbara Dilos; Julia LaMonica; Colleen Smith; Lillian Wong; Tania Lopez; Anju Galer; Stuart Kessle (Association of American Medical Colleges, 2019)
Introduction This multipatient simulation exercise encompasses triage by hospital medical providers during a mass casualty incident (MCI) involving gas line explosion with building collapse. The SimWars format allows two teams to participate in identical simulations coupled with active audience observation, followed by facilitated group discussion. The exercise requires real-time knowledge application of MCI management and helps learners develop a framework for rapidly classifying and dispositioning MCI patients. Methods Two teams of provider pairs completed MCI triage of 12 simulated patients in 8 minutes with an objective of quickly and accurately dispositioning within hospital bed availability. Participants included emergency medicine and surgery physicians, with active observation by mixed provider audiences. Observers completed a checklist per patient (category: urgent/emergent/not emergent, disposition: bed type/location). At simulation conclusion, a 45-minute facilitated discussion compared observers' self-assessment of MCI patient management with the simulation teams' decisions. Finally, an expert panel discussed management decisions and MCI triage pearls. Results Team performances (N = 4) and audience responses (N = 164) were similar on seven of 12 patients, allowing robust discussion. Participants completed an evaluation at exercise conclusion; 37% reported good/excellent ability to accomplish MCI initial triage and disposition before this exercise compared to 100% after, a statistically significant 63% increase. All postsurvey respondents agreed or strongly agreed that the exercise would change their MCI clinical practice. Discussion The two-team format allows comparison of how different teams handle MCI triage, and active observation allows comparison of audience and team decision making.